Effect of Tillage Practices on Chickpea Productivity in Rotation with Wheat under Rainfed Semi-arid Environment: Effect of Tillage Practices on Chickpea Productivity - Khattak, Mansoor Khan; Ullah, Fahim; Khattak, Muhammad Jamal; Wahab, Said; Saeed, Muhammad; Khan, Ijaz Ahmad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
Chickpea is an important legume crop worldwide. We investigated effect of five different tillage practices on soil physical properties, water use efficiency by chickpea and chickpea productivity in chickpea-wheat rotation. The soil was a sandy clay loam and seasonal rainfall during the study period ranged from 198 to 543 mm. Chickpea was sown in October and harvested in April. Mean maximum crop yield was obtained with chisel plough once plus tine type cultivator twice (CPTC2) (1968 kg ha-1) and mold board plough once plus tine type cultivator twice (MBTC2) (1736 kg ha-1) with water use efficiency of 6.93 kg ha-1 mm-1. Mean minimum yield was recorded in no-tillage (NT) (1695 kg ha-1) with water use efficiency of 5.56 kg ha-1 mm-1. Plots plowed with chisel plough once plus tine type cultivator twice (CPTC2) produced 16.28% and 17.66% more seed yield as compared to no-tillage (NT) and tine type cultivator three times (TC3, i.e., Farmer’s practice). Chickpea root development was better in plots plowed by chisel plough once and tine type cultivator twice (CPTC2) as compared to other tillage treatments. However, chickpea seed yield was poorly related to biomass yield. Overall, chisel plough once and tine type cultivator twice (CPTC2) was the most effective tillage treatment and produced more seed yield and conserved more moisture as compared to other tillage treatments in this sandy clay loam soil in located in a semi-arid environment.